Process parameter optimization for minimizing overcut in abrasive waterjet deep hole drilling of SS 316L - J. Bharani Chandar; N. Lenin; Alagar Karthick; Pradeep Kumar Singh; M. Siva Kumar; Md Irfanul Haque Siddiqui; Intesaaf Ashraf; Saurav Dixit; Nikolai Ivanovich Vatin; Choon Kit Chan (Scientific Reports)
Abstract The need for precise manufacturing in aerospace, medical, and automotive industries requires an investigation of upscale drilling methods that can achieve small-diameter deep holes with exceptional accuracy. Abrasive Waterjet Drilling (AWJD) has developed as a promising technology due to its distinctive blend of precision and adaptability. Despite several advantages, overcutting is the fundamental obstacle restricting the widespread use of AWJD. The novelty of this research is to investigate the impact of process parameters, specifically water pressure, standoff distance, and abrasive mass flow rate, on the top, bottom, and depth-averaged radial overcut developed during the deep hole drilling of stainless steel 316L material. The deep hole drilling experiments have been conducted utilizing Taguchi’s (L16) orthogonal array by adjusting the drilling settings. The statistical significance of specific drilling parameters and second-order quadratic models for the responses have been established by analysis of variance. Additionally, to mitigate the impact of overcut and improve the drilling quality necessary for diverse sectors such as automotive, biomedical, and oil and gas, a metaheuristic optimization method, specifically the Grasshopper Optimization Algorithm (GHO), has been utilized. Thereafter, the effectiveness of the suggested algorithm has been validated using quality measures, namely hyper-volume and spacing by comparing it to the approaches of whale optimization, harmony search, and multiverse optimization algorithms. The comparison shows that the GHO algorithm outperformed the others. The GHO algorithm identified the optimal process parameters for AWJD as water pressure 305.36 MPa, standoff distance 1.00 mm, and mass flow rate 600 g/min. The anticipated values for the top, bottom, and depth-averaged radial overcut, according to the optimal parameters, are 1.19 mm, 0.64 mm, and 1.53 mm, respectively. Furthermore, a validation test has been conducted to verify the efficacy of the GHO algorithm. The validation test showed top, bottom, and depth-averaged radial overcut values of 1.17 mm, 0.66 mm, and 1.49 mm, with percentage deviations of 1.71%, 3.03%, and 2.68%, respectively, with the GHO algorithm. The surface quality of the drilled holes has been examined through a Scanning Electron Microscope (SEM). The SEM images have been obtained at magnifications of 12X and 500X of the drilled hole surface using optimum parameters, demonstrating smooth and uniform surfaces at the top, middle, and bottom of the drilled hole.